Geopolitical risks shaping wireless technology value chains : Strategic responses to the U.S. industrial policies - Lindström, Noel (My University, 2025)
The current geopolitical landscape is characterized by growing polarization, protectionism, and increased regulatory interventions. Rising tensions between the United States and China coupled with the ongoing war in Ukraine have intensified concerns over national security, particularly in sectors deemed critical to societal functioning, such as wireless technologies. These technologies rely on complex global value chains (GVCs), which are increasingly vulnerable to political, regulatory, and strategic disruptions. Both, countries and companies are responding to geopolitical risks by seeking ways to protect and reconfigure these value chains. This thesis investigates how geopolitical risks influence the value chains of wireless technology companies with a specific focus on companies operating in the U.S. market. The research explores how companies seek to mitigate these risks through value chain reconfiguration. The literature review addresses three key areas: the nature of geopolitical risks and their relationship to industrial policies, the impact of such policies on firm-level decision-making, and the location-specific factors that guide GVC and production choices. The empirical part of the study consists of qualitative, semi-structured expert interviews with senior business executives from the wireless technology sector in both Europe and the United States. The data was analyzed using thematic analysis to identify key patterns and insights. The findings highlight that companies are decentralizing their value chains to countries approved under frameworks such as the Trade Agreements Act and Section 1260H list. These policies dictate compliance conditions for companies wishing to sell to the U.S. market, including terms on sourcing and supplier origin. Companies are also adopting procurement strategies that reduce dependence on any single supplier, thereby increasing resilience to external shocks and regulatory constraints. Furthermore, companies emphasize the importance of building trusted partnerships with reliable, compliant actors, which is essential in politically sensitive and security-focused markets. Overall, companies are prioritizing resilience, compliance with industrial policies and trust in their strategic responses. This study contributes to academic literature by integrating geopolitical risk, industrial policy and value chain theories into a cohesive analytical framework. It also offers practical insights by illustrating how companies operationalize these dynamics at a strategic and managerial level, an area that has received limited empirical attention. The results provide actionable guidance for business leaders navigating the complex regulatory and geopolitical landscape of the wireless technology sector.

Nykyistä geopoliittista tilannetta leimaa lisääntynyt polarisaatio, protektionismi ja sääntely. Yhdysvaltojen ja Kiinan kiristyneet suhteet sekä meneillään oleva sota Ukrainassa ovat lisänneet huolta kansallisesta turvallisuudesta erityisesti yhteiskunnan kannalta kriittisillä aloilla, kuten langattomassa teknologiassa. Langattomat teknologiat ovat riippuvaisia monimutkaisista globaaleista arvoketjuista, jotka ovat entistä alttiimpia poliittisille sääntelyyn liittyville ja muille häiriöille. Sekä valtiot, että yritykset etsivät keinoja näiden arvoketjujen suojaamiseksi ja uudelleenjärjestämiseksi. Tämä tutkimus tarkastelee, miten geopoliittiset riskit vaikuttavat langattoman teknologian yritysten arvoketjuihin, keskittyen erityisesti Yhdysvaltojen markkinoilla toimiviin yrityksiin. Tutkimus tarkastelee, miten yritykset pyrkivät lieventämään geopoliittisia riskejä arvoketjujaan uudelleenjärjestelemällä. Kirjallisuuskatsaus keskittyy kolmeen keskeiseen osa-alueeseen: geopoliittisten riskien luonteeseen ja niiden suhteeseen teollisuuspolitiikkaan, teollisuuspolitiikan vaikutuksiin yritysten päätöksentekoon sekä sijaintiin liittyviin tekijöihin, jotka ohjaavat globaaleja arvoketjuja ja tuotantopäätöksiä. Tutkimuksen empiirinen osio on toteutettu laadullisilla puolistrukturoiduilla asiantuntijahaastatteluilla. Haastateltavat ovat langattoman teknologian alan kokeneita yritysjohtajia Euroopasta ja Yhdysvalloista. Haastatteluaineisto on analysoitu temaattisesti keskeisten ilmiöiden tunnistamiseksi. Tulokset osoittavat, että yritykset hajauttavat arvoketjujaan maihin, jotka kuuluvat Yhdysvaltojen sääntelyn kuten TAA ja Section 1260H -listan hyväksymiin alueisiin. Nämä regulaatiokehykset määrittelevät ehdot, joiden mukaisesti yritykset voivat toimittaa tuotteitaan Yhdysvaltojen markkinoille. Yritysten täytyy täyttää vaatimukset esimerkiksi komponenttien alkuperästä ja toimittajista. Yritykset käyttävät myös hankintastrategioita, jotka vähentävät riippuvuuksia yksittäisistä toimittajista ja näin lisäävät joustavuutta ulkoisia häiriöitä ja sääntelyä kohtaan. Tämän lisäksi yritykset pyrkivät luomaan luotettavia kumppanuuksia sellaisten toimijoiden kanssa, jotka täyttävät sääntelyvaatimukset ja joiden toimintaan voidaan luottaa. Tämä on tärkeää erityisesti poliittisesti herkillä ja turvallisuuskriittisillä sektoreilla. Yritysten strategiset valinnat pohjautuvatkin yhä enemmän selviytymiskyvyn, sääntelyn noudattamisen ja luottamuksen varaan. Tutkimus luo lisäarvoa nykyiselle tieteelle yhdistämällä geopoliittisen riskin, teollisuuspolitiikan ja arvoketjuteorian yhtenäiseksi analyyttiseksi viitekehykseksi. Lisäksi se tarjoaa käytännönläheisiä näkemyksiä siitä, miten yritykset voivat hallita sääntelyn tuomia muutoksia käytännön tasolla. Tulokset tarjoavat konkreettisia ohjeita yritysjohtajille, jotka toimivat langattoman teknologian sääntelyllisesti monimutkaisessa ja geopoliittisesti herkistyneessä toimintaympäristössä.
Keywords: geopolitical risk, industrial policy, global value chains, OLI, international business, United States, geopoliittinen riski, teollisuuspolitiikka, globaalit arvoketjut, OLI, kansainvälinen liiketoiminta, Yhdysvallat